A conceptual idea of four steps four layers framework for online 3D visualization in agricultural application - Saha, Gonesh Chandra; Che Mat, Ruzinoor (American Scientific Publishers, 2019)
Agricultural plantation management is an important stage of agricultural technology development. The goal of this research article is to present and justify an identified research problem with the utilization of a proposed Four Steps Four Layers (4S4L) framework for online based 3D visualization application. The identified research problem was investigated since the current 3-layer framework has shortcomings, such as, weaknesses in the size of graph visualization where the graph size can make a typically decent layout algorithm totally unusable. In our novel approach, we have proposed a client/server structure based framework which subdivides the total process into the concept of layer to overcome the existing issue. One more layer will be added to the existing three layer framework to formalize into 4S4L framework for handling the graph visualization. The potential of the proposed framework also is expected to enhance online 3D visualization, and it will also be adapted for training professionals, decision makers and education students, as well as advancing precision technologies.